2009
DOI: 10.1186/1472-698x-9-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

The role of supportive supervision on immunization program outcome - a randomized field trial from Georgia

Abstract: BackgroundOne of the most common barriers to improving immunization coverage rates is human resources and its management. In the Republic of Georgia, a country where widespread health care reforms have taken place over the last decade, an intervention was recently implemented to strengthen performance of immunization programs. A range of measures were taken to ensure that immunization managers carry out their activities effectively through direct, personal contact on a regular basis to guide, support and assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 11 publications
4
46
1
Order By: Relevance
“…The MANIFEST approach demonstrated that it is possible to have positive and collegial relationships between health workers and supervisors. The changes in the use of support supervision in improving the quality of maternal and newborn care services has also been reported by other studies conducted in low-income countries [10,1214]. …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The MANIFEST approach demonstrated that it is possible to have positive and collegial relationships between health workers and supervisors. The changes in the use of support supervision in improving the quality of maternal and newborn care services has also been reported by other studies conducted in low-income countries [10,1214]. …”
Section: Discussionsupporting
confidence: 68%
“…Support supervision also provides opportunities for regular feedback and therefore promotes skill building through appropriate strategies, such as training and mentorships [12,13]. Inadequate support supervision has been cited as a key contributor to health worker shortages in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…The supportive supervision by NGO workers through semi-monthly visits provided them with a structured learning process. Similar to other low-and middle-income country settings, more hands-on support through supportive supervision imparted more confidence, knowledge and skills in CHWs and thereby improved their motivation to perform [13][14][15][16]. Further, the supervisors provided the conduit for efficient communication between the CHWs and the formal health system to maintain an uninterrupted supply of commodities.…”
Section: Discussionmentioning
confidence: 97%
“…Communities should be empowered to regularly monitor and evaluate the effectiveness of interventions [8]. In terms of the involvement of CHW, the global evidence suggests that regular and systematic supervision with clearly defined objectives can improve the performance of community health workers involved in primary health care [13][14][15][16]. Such evidence for India, however, is lacking and insufficient community capacity, trust, and coordination may keep the new malaria control strategies from meeting expected outcomes [9,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This may contribute beneficially to sustenance of health education and training that might have been provided for the patients/clients. Djibuti et al (2009) defined supportive supervision as "range of measures to ensure that personnel carry out their activities effectively through direct personal contact on a regular basis to guide, support and assist designated staff to become more competent in their work." This type of supervision can also be adapted for guiding, supporting and assisting the health care consumers to develop selfefficiency in their self-care in the spirit of promoting good health and preventing diseases.…”
Section: Introductionmentioning
confidence: 99%